O Brasil e a Antártica : um estudo do papel do Itamaraty na estrutura do Programa Antártico Brasileiro (PROANTAR) - Silva, Adler Lucas Pinheiro da (2025)
Antarctica is a continent with vast territorial extension and immeasurable potential. The strategic, environmental and political importance has been demonstrated since the first occupations of the polar region and has attracted the world's attention in contemporary times. Brazil is a supporter of the Antarctic Treaty System (ATS) and has had an institutional structure since 1975. Despite this, the country is not recognized for making significant efforts on the subject. Thus, this paper aims to analyze the commitment of the Ministry of Foreign Affairs (MRE) to Antarctica, based on the exploration of the historiography of Brazil in Antarctica, giving centrality to aspects of foreign policy, adherence to the ATS and the institutionality of Antarctic policies. Thus, we can observe that the participation of Itamaraty is established in an auxiliary or consultative manner, with low participation and non-centrality of the institution for Antarctica. In contrast, there is strong participation and centrality of the Brazilian Navy in the management of Antarctic objectives, which has lasted since the creation of the Interministerial Commission for Sea Resources (CIRM).